Offshore validation of a 3 km ERA‐Interim downscaling—WRF model's performance on static stability. Issue 3 (16th April 2015) - Barstad, Idar
Abstract: In the evaluation of performance of numerical models, static stability has gained less interest and attention than many other atmospheric parameters. Nevertheless, this parameter may in fact have rather large implications as it controls such features as gravity waves and turbulence. In this paper, a closer look has been taken at the behavior of static stability in a 3 km gridded numerical downscaling of the ERA‐Interim reanalysis. The simulation performed with the Weather Research and Forecasting model has been nudged towards large scale analysis (spectral nudging) and satellite‐derived ocean surface winds (Quick Scatterometer). The validation of low‐level static stability was conducted in the North Sea using data from the FINO1 mast for year 2008, and a deeper part of the atmosphere was validated using the Ekofisk oil platform radiosonde data for years 2007–2010. The offshore mast comparison shows that the model over‐predicts the number of unstable cases and that the unstable cases are not unstable enough. The model simulated a clear dependency between vertical wind shear and static stability; however, this was not the case in the observations. The model produced too few events with weak turbulence, but rather put the emphasis on intermediate turbulent intensities. With the radiosonde data measuring the static stability over a deeper part of the atmosphere, similar results as for lower levels showed. In addition, the temperature gradient across the inversion at the boundary layer top was too shallow in the model, potentially letting too much wave energy escape the boundary layer. © 2015 The Authors Wind Energy Published by John Wiley & Sons Ltd.